Archaeometric study of possible Ninevite‐5 pottery from upper Tigris region using SEM‐EDS, PEDXRF, and OM. (29th October 2017) - Bayazit, Murat
Abstract : This study aims to reveal the production technology of some representative samples of possible Ninevite‐5 potsherds which are generally dated between the Early Jezirah I to EJ‐II/EJ‐III periods (roughly 3000–2500 bc ) and accepted as the typical ceramics reflecting the northern Mesopotamian culture in the first half of the 3rd millennium BC. The samples were selected from the archeological excavation area of Kuriki (upper Tigris region, Turkey) and exposed to multiple analytical techniques including scanning electron microscopy with an energy dispersive spectrometer, optical microscopy, and polarized energy dispersive X‐ray fluorescence spectrometry. The results showed that all the samples have high amounts of CaO (up to 29.83 wt.%) indicating use of calcareous clay deposits and they have an analogous chemical compositions in terms of both major oxides and trace elements which implied the use of the same raw materials. The vitrification degrees of the samples, examined by back scattered electron images, suggested that the firing temperature of the potsherds did not exceed the range of 800–900°C. It was also revealed that the firing atmosphere was oxidative which would be attributed to use of kiln firing rather than a bonfire or pit firing. Both the chemical and petrographic results suggested that the investigated samples presumably belong to a regional (upper Tigris) production rather than a local one.